Harnessing Tolerogenic Histone Peptide Epitopes From Nucleosomes for Selective Down-Regulation of Pathogenic Autoimmune Response in Lupus (Past, Present, and Future) - Datta, Syamal K. (Frontiers in Immunology, 2021)
Autoantigen-directed tolerance can be induced by certain nucleosomal histone peptide epitope/s in nanomolar dosage leading to sustained remission of disease in mice with spontaneous SLE. By contrast, lupus is accelerated by administration of intact (whole) histones, or whole nucleosomes in microparticles from apoptotic cells, or by post-translationally acetylated histone-peptides. Low-dose therapy with the histone-peptide epitopes simultaneously induces TGF beta and inhibits IL-6 production by DC in vivo, especially pDC, which then induce CD4+CD25+ Treg and CD8+ Treg cells that suppress pathogenic autoimmune response. Both types of induced Treg cells are FoxP3+ and act by producing TGF beta at close cell-to-cell range. No anaphylactic adverse reactions, or generalized immunosuppression have been detected in mice injected with the peptides, because the epitopes are derived from evolutionarily conserved histones in the chromatin; and the peptides are expressed in the thymus during ontogeny, and their native sequences have not been altered. The peptide-induced Treg cells can block severe lupus on adoptive transfer reducing inflammatory cell reaction and infiltration in the kidney. In Humans, similar potent Treg cells are generated by the histone peptide epitopes in vitro in lupus patients’ PBMC, inhibiting anti-dsDNA autoantibody and interferon production. Furthermore, the same types of Treg cells are generated in lupus patients who are in very long-term remission (2-8 years) after undergoing autologous hematopoietic stem cell transplantation. These Treg cells are not found in lupus patients treated conventionally into clinical remission (SLEDAI of 0); and consequently they still harbor pathogenic autoimmune cells, causing subclinical damage. Although antigen-specific therapy with pinpoint accuracy is suitable for straight-forward organ-specific autoimmune diseases, Systemic Lupus is much more complex. The histone peptide epitopes have unique tolerogenic properties for inhibiting Innate immune cells (DC), T cells and B cell populations that are both antigen-specifically and cross-reactively involved in the pathogenic autoimmune response in lupus. The histone peptide tolerance is a natural and non-toxic therapy suitable for treating early lupus, and also maintaining lupus patients after toxic drug therapy. The experimental steps, challenges and possible solutions for successful therapy with these peptide epitopes are discussed in this highly focused review on Systemic Lupus.